A new hybrid MCDM method for optimizing natural stone se-lection for building envelopes - Ulutaş, Alptekin; Balo, Figen; Topal, Ayse (Revista de la Construcción. Journal of Construction, 2024)
Most kinds of natural stones are perfect coating materials. Through utilizing stones with less thermal conductivity coefficients, isolation of constructions improves with energy effective resolution. Modern building technologies prefer either decreasing stone to the weakest plausible extents or utilizing natural stones because natural stones have lower thermal conductivity with lighter weights. For this reason, first, the thermal and physical characteristics of natural stones used as coating material on the exterior walls of the buildings were investigated in this study. Then, in the light of these characteristics, natural stones with the best performance in terms of energy efficiency were determined using multi-criteria decision-making methods including FFSWARA and COBRA. The findings show that compressive strength is the most significant criteria and Isparta andesite stone is the most superior natural stone in terms of performance. This study contributes to the literature in three ways. First, the COBRA method used in this study has recently been introduced to the literature. Therefore, it has not been covered much in the literature. Second, this method has not been used in the selection of natural stone selection in the literature to our best knowledge. Third, this method has not been used together with the FFSWARA method before.